Prevalence of respiratory disease in the population of Queensland communities in proximity to coal mines and coal mining activities - Karatela, Shamshad; Caruana, Samantha; Paul, Gunther (International Journal Of Community Medicine And Public Health, 2022)
Air quality related to respiratory illness is examined in many settings, including populations that work or reside close to sources of pollution. Industry produced pollution from mining and metal manufacturing, natural environmental pollution as in the case of bushfires and large-scale dust storms are examples. We reviewed any available literature and data concerning the Queensland coal industry and its effect on respiratory health of miners, mining related workers and communities in proximity to coal mines. We searched various databases using keywords related to coal and respiratory diseases, using the five step criteria defined by Denyer and Tranfield. In the Queensland coal mining industry, the negative effect of mining on workers’ respiratory health has been known for many years and has received increased attention in the last five years both nationally and internationally due to the resurgence in Coal Mine Dust Lung Diseases and specifically Coal Worker’s Pneumoconiosis (CWP). A Queensland parliamentary review has prompted regulatory amendments for the permitted (occupational) exposure level (PEL; OEL) to coal dust and silica; amendments have also been enacted for better occupational respiratory health surveillance of Queensland coal miners, both surface and underground. Considering Queensland has a high proportion of Australian coal mines, the literature available on respiratory health in Queensland coal mines and surrounding communities is minimal. There is very limited research into, and possible underreporting of CMDLD amongst the coal mining workers in Queensland. Further studies are required to better understand air pollution and health effects in coal miners in Queensland.